2016
DOI: 10.1515/ppb-2016-0050
|View full text |Cite
|
Sign up to set email alerts
|

Perceived competence and warmth influence respect, liking and trust in work relations

Abstract: Many studies confirmed the positive effect of trust on human relations and performance in organizations. As a social judgment, trust should be related to perceived competence and warmth as two basic dimensions of person perception. Surprisingly, to date no attempts have been made to examine the influence of attributed competence and warmth on social judgments in interpersonal relations at work. To this end, we examine the influence of perceived competence and warmth on trust, liking and respect in upward and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Based upon social identity theory, a considerable body of research shows that behaviors which communicate an individual's standing or status, corresponds to an individual feeling respected (appraisal respect) (Tyler & Blader, 2003). tal study found that behaviors conveying warmth had a stronger effect than those conveying competence on perceptions of liking, whilst the opposite was the case for appraisal respect (Oleszkiewicz & Lachowicz-Tabaczek, 2016). Based on these status and competence arguments, we would expect both these influence tactics to positively affect mutual appraisal respect rather than mutual recognition respect.…”
Section: F I G U R E 1 Upward Influence Tactics Direct Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…Based upon social identity theory, a considerable body of research shows that behaviors which communicate an individual's standing or status, corresponds to an individual feeling respected (appraisal respect) (Tyler & Blader, 2003). tal study found that behaviors conveying warmth had a stronger effect than those conveying competence on perceptions of liking, whilst the opposite was the case for appraisal respect (Oleszkiewicz & Lachowicz-Tabaczek, 2016). Based on these status and competence arguments, we would expect both these influence tactics to positively affect mutual appraisal respect rather than mutual recognition respect.…”
Section: F I G U R E 1 Upward Influence Tactics Direct Effectsmentioning
confidence: 94%
“…Both the supervisor feeling respected and respecting their subordinate, should together contribute to mutual appraisal respect. A recent experimental study found that behaviors conveying warmth had a stronger effect than those conveying competence on perceptions of liking, whilst the opposite was the case for appraisal respect (Oleszkiewicz & Lachowicz‐Tabaczek, ). Based on these status and competence arguments, we would expect both these influence tactics to positively affect mutual appraisal respect rather than mutual recognition respect.Hypothesis Ingratiation and self‐promotion will be positively associated with mutual appraisal respect .…”
Section: Influence Tactics Predict Mutual Recognition Respect and Mutmentioning
confidence: 99%
“…To estimate the required sample size, we conducted a power analysis using G*Power software (Faul, Erdfelder, Buchner, & Lang, ). We estimated the effect size at partial η 2 = 0.03 on the basis of research conducted by Oleszkiewicz and Lachowicz‐Tabaczek () who reported a significant effect of the warmth by power interaction on workplace trust, using a 2 × 2 × 2 experimental design. With the conventionally assumed power of 0.80 and α = 0.05, the required sample size to detect this effect was N = 256.…”
Section: Studymentioning
confidence: 99%
“…Agentic individuals are assessed as positively as communal individuals in strong ties, and they benefit from higher social status and respect which increases their potential for affiliation at large (Wojciszke et al, 2009 ; Carrier et al, 2014 ). Communion and agency are related to a comparable extent with higher other-rated trust for the target (Oleszkiewicz and Lachowicz-Tabaczek, 2016 ). We hypothesize that communion (Hypothesis 2a) and agency (Hypothesis 2b) are positively related with belongingness.…”
Section: Hypothesesmentioning
confidence: 99%